Out-of-hospital cardiac arrest treated by emergency medical service teams during COVID-19 pandemic: A retrospective cohort study - Borkowska, Magdalena J. (Cardiol J, 2021)
BACKGROUND: Out-of-hospital cardiac arrest (OHCA) is a challenge for medical personnel, especially in the current COVID-19 pandemic, where medical personnel should perform resuscitation wearing full personal protective equipment. This study aims were to assess the characteristics and outcomes of adults who suffered an OHCA in the COVID-19 pandemic treated by emergency medical service (EMS) teams. METHODS: All EMS-attended OHCA adults over than 18 years in the Polish EMS registry were analyzed. The retrospective EMS database was conducted. EMS interventions performed between March 1, and April 30, 2020 were retrospectively screened. RESULTS: In the study period EMS operated 527 times for OHCA cases. The average age of patients with OHCA was 67.8 years. Statistically significantly more frequently men were involved (64.3%). 298 (56.6%) of all OHCA patients had resuscitation attempted by EMS providers. Among resuscitated patients, 73.8% were cardiac etiology. 9.4% of patients had return of spontaneous circulation, 27.2% of patients were admitted to hospital with ongoing chest compression. In the case of 63.4% cardiopulmonary resuscitation was ineffective and death was determined. CONCLUSIONS: The present study found that OHCA incidence rate in the Masovian population (central region of Poland) in March–April 2020 period was 12.2/100,000 adult inhabitants. Return of spontaneous circulation in EMS was observed only in 9.4% of resuscitated patients. The presence of shockable rhythms was associated with better prognosis. The prehospital mortality, even though it was high, did not differ from those reported by other studies.